Electrical–Thermal Aging Performance of PAH-Modified Interfacial Coating Agent for HVDC Cable Accessory - Wenbo Zhu; Kaulya Pathiraja; Xu Guo; Baojun Hui; Mingli Fu; Linjie Zhao; Yuhuai Wang; Jin Li (Energies)
A novel interfacial coating agent was developed by modifying silicone oil with polycyclic aromatic hydrocarbons (PAHs) to enhance the insulation performance of HVDC cable accessories. This study investigates the effects of corona and hot–cold cycle aging on the DC breakdown characteristics of the Cross-Linked Poly Ethylene and Ethylene Propylene Diene Monomer (XLPE/EPDM) interface. Interfacial breakdown tests, infrared spectroscopy, and a microstructural analysis were employed to investigate aging mechanisms. The results show that PAH-modified silicone oil significantly increases the breakdown voltage, with 2,4-dihydroxybenzophenone (C13H10O3) identified as the optimal additive via quantum chemical calculations (QCCs). Even after aging, the modified interface maintains its superior performance, confirming the long-term reliability of the coating.